دراسة الانتباه البصري لدى عينة من الأطفال المصابين بمرض الصرع الفص الصدغي دراسة ميدانية بولاتيي الأغواط و البيض - نعيمة بعيط; أسماء فضيلة بوران; مداني بن يحي (My University, 2022)
The current study aimed to shed light on the study of visual attention in a sample of children with temporal lobe epilepsy, and the sample consisted of 06 children ranging in age from five to ten